2019
DOI: 10.52282/icr.v10i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Combating Fake News, Misinformation, and Machine Learning Generated Fakes: Insight's from the Islamic Ethical Tradition

Abstract: The growing trend of sharing and acquiring news through social media platforms and the World Wide Web has impacted individuals as well as societies, spreading misinformation and disinformation. This trend—along with rapid developments in the field of machine learning, particularly with the emergence of techniques such as deep learning that can be used to generate data—has grave political, social, ethical, security, and privacy implications for society. This paper discusses the technologies that have led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In light of this, the relationship between the narrators is critical in assessing the hadith's rank. The investigation established that fraudulent narrators originate and distribute every bogus hadith (Sookhdeo, 2006;Zubair, Raquib, & Qadir, 2019). Thus, religious scholars can contribute to and play a role in combating the spread of falsified hadiths.…”
Section: The Fabricated Hadith: the Deadly Virus In The Treasury Of I...mentioning
confidence: 99%
“…In light of this, the relationship between the narrators is critical in assessing the hadith's rank. The investigation established that fraudulent narrators originate and distribute every bogus hadith (Sookhdeo, 2006;Zubair, Raquib, & Qadir, 2019). Thus, religious scholars can contribute to and play a role in combating the spread of falsified hadiths.…”
Section: The Fabricated Hadith: the Deadly Virus In The Treasury Of I...mentioning
confidence: 99%
“…Some fake news is unintentionally published or shared and is called misinformation [ 43 ]. Repeated viewing of fake news makes it familiar to the recipient, makes it believable, and causes it to be circulated as real news [ 44 ]. However, it becomes difficult to distinguish between fake news and real news, as scientific research has revealed that the human ability to distinguish between true and false information is relatively weak, with a rate of about 54% [ 45 ].…”
Section: Background Of Studymentioning
confidence: 99%
“…Nevertheless, most of the authors did not highlight the need to provide security and privacy to the user's confidential information. For example, Zubair et al [10] explored about combating the fake news according to the islamic ethical tradition. The review has analyzed the Islamic guidelines to detect fake news (misinformation) and machine learning generated fakes.…”
Section: Scope Of the Surveymentioning
confidence: 99%